Growth and Production Super 1 Variety Sweet Sorghum in Different Time and Dosage of ZA Fertilizer Application (Jurnal Pertanian Terpadu, 2020)
Nitrogen fertilization affects the growth of sorghum plants, grain yields, biomass and brix sugar content, so that the suitable time and dosage is needed to arrange. The purpose of the study was to determine the application time and fit dose of ZA fertilizer on the yield  (t/ha), and other agronomic characteristics. The study was conducted in the Experimental Field of the Indonesian Cereals Plant Research Institute, Maros, South Sulawesi in August - November 2016. The experiment was arranged based on a two-factor randomized block design with three replications. The first-factor was the four time ZA fertilizer application, which was placed on the age of 40 days after planting, 50 days after planting, 60 days after planting and 70 days after planting. The second factor was the four doses of ZA fertilizer namely 0 kg/ha, 50 kg/ha, 75 kg/ha. The sorghum variety used in this study was Super 1. The results showed that the interaction between treatments had a very significant effect on seed production/ha with the highest yield of 3.30 tons/ha in the 50 kg/ha fertilizer application applied at the age of 40 DAP (days after planting). The response of plants to the independent treatment factor when fertilizing application had a very significant effect on plant height (35 HST and 105 HST), stem diameter, number of nodes and biomass weight (t/ha), and significantly affected the weight of 1000 seeds. Fertilizer dosage significantly affects seed production per ha, panicle length and volume of sap. Pearson correlation between observations variables with seed yield per hectare showed high and very significant results in stem diameter (r = 0.74), as well as in the variable number of sections (r = 0.65). Stem diameter has the biggest direct effect on seed production per hectare with a cross print coefficient of 0.75.
Keywords: ZA fertilizer, Sweet sorghum, Dry land, Super 1, Pathway